DETERMINATION OF OPTIMUM COATING SURFACING PARAMETERS BY ELECTRO-CONTACT FLASHING METHOD - K. E. Beljavin; A. V. Sosnovsky (Наука и техника)
The paper presents a calculation of technological surfacing modes using an electro-contact flashing method. In order to make calculations a mathematical model of surfacing process based on an analysis of heat exchange between a part heated by the electro-contact method and a metallic powder flashed by it has been developed in the paper. The paper contains an optimization of the technological modes that allows to improve quality of the obtained coating.